2018
DOI: 10.1002/jcb.27704
|View full text |Cite
|
Sign up to set email alerts
|

LINC01133 aggravates the progression of hepatocellular carcinoma by activating the PI3K/AKT pathway

Abstract: LncRNAs exhibit crucial roles in various pathological diseases, including hepatocellular carcinoma (HCC). Therefore, it is significant to recognize the dysregulated lncRNAs in HCC progression. Recently, LINC01133 has been identified in several tumors. However, the biological role of LINC01133 in HCC remains poorly understood. Currently, we focused on the function of LINC01133 in HCC development. We observed that LINC01133 was significantly increased in HCC cells including HepG2, Hep3B, MHCC-97L, SK-Hep-1, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…In previous studies, C/EBPβ-LINC01133 axis was found to promote proliferation of pancreatic ductal adenocarcinoma cells by upregulating CCNG1 [24]. In addition, LINC01133 was found to aggravate the progression of hepatocellular carcinoma and non-small cell lung cancer by activating the PI3K/ATK pathway or by repressing KLF2/E-cadherin [25,26]. Conversely, LINC01133 was reported to act as a tumor suppressor in the context of gastric cancer, which was downregulated in tumor cells and acts as a ceRNA by sponging miR-106a-3p to regulate APC expression and Wnt/β-catenin pathway [27,28].…”
Section: Discussionmentioning
confidence: 93%
“…In previous studies, C/EBPβ-LINC01133 axis was found to promote proliferation of pancreatic ductal adenocarcinoma cells by upregulating CCNG1 [24]. In addition, LINC01133 was found to aggravate the progression of hepatocellular carcinoma and non-small cell lung cancer by activating the PI3K/ATK pathway or by repressing KLF2/E-cadherin [25,26]. Conversely, LINC01133 was reported to act as a tumor suppressor in the context of gastric cancer, which was downregulated in tumor cells and acts as a ceRNA by sponging miR-106a-3p to regulate APC expression and Wnt/β-catenin pathway [27,28].…”
Section: Discussionmentioning
confidence: 93%
“…In researching the possible carcinogenic mechanism of m1A-related regulatory genes in HCC, PI3K/Akt signaling pathway was found to be the most important item through KEGG analysis. The PI3K/Akt signaling pathway has been reported to involve in proliferation and anti-apoptosis process in HCC 40,41 , which pointed out a theoretical basis for further mechanism research on m1A-related regulatory genes. Following, relevant validations via cell and animal experiment are crucial to carry out to reveal how m1A-related regulatory genes regulate PI3K/Akt pathway in HCC.…”
Section: Discussionmentioning
confidence: 93%
“…Numerous studies have indicated that the lncRNA LINC01133 serves as a regulator of various cancer types; for example, LINC01133 was revealed to suppress the invasiveness, migration and proliferation of nasopharyngeal carcinoma cells, via interaction with Y box binding protein 1 (48). Furthermore, Zheng et al (49) demonstrated that LINC01133 contributes to the progression of HCC via activation of the PI3K/AKT pathway. It has also been identified that LINC01133 was upregulated in lung squamous cell cancer cells and was associated with poorer overall survival outcomes (50).…”
Section: Discussionmentioning
confidence: 99%